Efecto de nanopartículas de plata sobre la capacidad de regeneración de Dugesia tigrina - Ramírez Huamán, Oswaldo José (2018)
The present investigation determined the effect of four silver nanoparticles concentrations (0%, 25%, 50% and 100%) on the regeneration capacity of Dugesia tigrina making different cuts of transversal, longitudinal and double transversal type, which origined the fragments of the upper and lower part, left and right fragments, and cephalic, middle and caudal fragments, respectively. This sections were exposed to the different concentrations of NPs-Ag, the time of visible blastema formation and the individual total formation were measured. A stereocope was used to observe and register the different stages of the regeneration process. It was determined that treatment T4 (100% AgNPs) produced the major reduction of blastema formation in hours, being the upper section (block I) the one that developed blastema in less time (79 hours). In addition, the treatment T4 (100% AgNPs) produced the major reduction of individual total formation in hours, standing out the left section, in which complete individuals developed in less time (163,50 hours). Moreover, it was observed that the higher the concentration of silver nanoparticles, the higher the number of dead individuals finding a high percentage on treatment T4. Finally, the variance analysis revealed the presence of statiscally significant differences.